STRATEGIES AND METHODOLOGICAL CONSIDERATIONS IN CHOOSING A RESEARCH SAMPLE (Annual of the Faculty of Philosophy in Skopje, 2023)
The text defines the fundamental terms relevant to the process of sampling, elaborates the characteristics of individual samples, selection strategies, and the key methodological issues and dilemmas of the researchers during the procedures of sampling.The selection of a sample is an essential aspect when planning the methodology of empirical research and has a key role in ensuring the reliability and validity of research results. Researchers should carefully consider the characteristics of the population and the specific research objectives and accordingly choose the sampling strategy.Representative samples minimize bias and provide a higher level of confidence when generalizing results to a larger population. Non-representative samples are valuable when the selection of a representative sample is impractical or impossible. They involve different forms of bias but offer flexibility, cost-effectiveness and practicality. Non-representative samples are applicable in qualitative studies and in the research with populations that are hard to reach. However, it is important to be aware of their limitations and the justification for generalization findings outside the specific sample.Regardless of the used strategy, researchers must strive for transparency, clearly documenting the unit selection procedure and stress the potential limitations as key elements to ensure the reliability and validity of the research results.
Keywords: methodology; representative samples; non-representative samples